Age at menarche and late adolescent adiposity associated with mammographic density on processed digital mammograms in 24,840 women - Alexeeff, Stacey E. (Cancer Epidemiol Biomarkers Prev, 2017)
BACKGROUND: High mammographic density is strongly associated with increased breast cancer risk. Some, but not all, risk factors for breast cancer are also associated with higher mammographic density. METHODS: The study cohort (N=24,840) was drawn from the Research Program in Genes, Environment and Health of Kaiser Permanente Northern California and included non-Hispanic white females aged 40–74 years with a full-field digital mammogram (FFDM). Percent density (PD) and dense area (DA) were measured by a radiological technologist using Cumulus. The association of age at menarche and late adolescent BMI with PD and DA were modeled using linear regression adjusted for confounders. RESULTS: Age at menarche and late adolescent BMI were negatively correlated. Age at menarche was positively associated with PD (p-value for trend<0.0001) and DA (p-value for trend <0.0001) in fully adjusted models. Compared to the reference category of age 12–13 years at menarche, menarche at age >16 years was associated with an increase in PD of 1.47% [95% CI: (0.69, 2.25)] and an increase in DA of 1.59cm(2) [95% CI: (0.48, 2.70)]. Late adolescent BMI was inversely associated with PD (p-value <0.0001) and DA (p-value <0.0001) in fully adjusted models. CONCLUSIONS: Age at menarche and late adolescent BMI are both associated with Cumulus measures of mammographic density on processed FFDM images. IMPACT: Age at menarche and late adolescent BMI may act through different pathways. The long-term effects of age at menarche on cancer risk may be mediated through factors besides mammographic density.